A comparative analysis of the translation of harf al waw in Surah Maryam verse 1-40 by Abdullah Yusuf Ali and Tahereh Saffarzadeh - Intan Nurjannah (Fak. Adab dan Ilmu Budaya UIN Sunan Kalijaga, 2015)
st,1/ws.c.1